PENGEMBANGAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN KEMAMPUAN MENULIS KEMBALI PADA TEMA TUMBUHAN DAN HEWAN SISWA KELAS III SDN 105350 PERBARAKAN - Yulinda Fatma Sari; Arrini Shabrina Anshor (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is a development in the form of audio visuals as learning media which aims to 1) determine the feasibility and produce learning media products for writing stories by material experts and media experts according to the needs of students and teachers. 2) Knowing the responses of students and teachers to the audio visual learning media developed. 3) Knowing the success of audio visual media by using tests to improve writing skills on the theme of loving plants and animals for class III students. This research method is Research and Development (R&D) with ADDIE development stages, namely analysis, design (planning), development (development), implementation (implementation), evaluation (evaluation). This research was carried out up to the evaluation stage, but the evaluation carried out was only a limited trial, so the evaluation referred to here is an evaluation of implementation activities. The evaluation results were obtained from teacher and student suggestions during the trial. Media validation is carried out by material experts, media experts. The media developed was tested by 31 class III students at SDN 105350 Perbarakan. The percentage material expert assessment results obtained were 90.90% which was included in the "very valid" category. The results of the media expert assessment obtained a percentage of 81.53% which was included in the "very valid" category. The percentage of student responses in the learning media questionnaire obtained was 92.96% which was included in the "very valid" category. And the assessment of tests carried out by students on learning media to improve students' ability to rewrite stories obtained a percentage of 79.83% "valid". Thus, audio visual learning media was successfully used to improve students' writing skills on theme 2, love plants and animals as a learning medium.